Labor productivity and energy use in a three sector model: An application to Egypt - Rudiger von Arnim; Codrina Rada (The University of Utah, Department of Economics, 2011)
This paper presents a model of a developing economy with three sectors - a modern sector producing manufactures and services, a traditional sector producing agricultural goods, and a third sector providing energy. Modern and energy sector are assumed to be demand-constrained; the agricultural sector is supply-constrained. Simulation exercises confirm insights of existing theory on structural heterogeneity: A price-clearing agricultural sector can impose an inflationary barrier on growth. Further, emphasis is placed on the sources of productivity growth. Specifically, higher energy intensity rather than increases in energy productivity enable labor productivity growth, with the attendant complications for 'green growth'.
Keywords: O41; Q43; C63; 330; Structural heterogeneity; Multi-sector model; Energy use